Stroke survivors' occupational performance and cognitive strategy use: A pilot exploration of strengths and difficulties using the Perceive Recall Plan Perform System of Task Analysis. - White, Jocelyn; Nott, Melissa T; Barr, Chris; Chapparo, Christine J; George, Stacey (British Journal of Occupational Therapy, 2020)
Introduction: The Perceive Recall Plan Perform System of Task Analysis is an ecological assessment of occupational performance and cognitive strategy application. This study aimed to describe occupational performance and cognitive strategies of stroke survivors in an early supported discharge service, compare the assessment with global measures of function and evaluate the feasibility of implementing the assessment in the early supported discharge setting. Method: This study was a pilot study design and used consecutive sampling. Participants were assessed with the Perceive Recall Plan Perform System of Task Analysis and two global measures: the Functional Independence Measure and the Australian Modified Lawton's Instrumental Activities of Daily Living Scale. Scores from the Perceive Recall Plan Perform System of Task Analysis were analysed by task mastery, sub-quadrants and quadrants, and correlations between the assessment and global measures were examined. Findings: In this cohort (n = 10), the Perceive Recall Plan Perform System of Task Analysis assessment required 47 minutes per task and identified reduced task mastery (mean = 55%, SD = 10%) with common difficulties in the perceive and plan domains. High to moderate correlations were identified between the plan quadrant and global measures (p < 0.05). Conclusion: Perceive Recall Plan Perform System of Task Analysis assessment can be successfully implemented by occupational therapists with stroke survivors receiving early supported discharge to measure occupational performance and identify strengths and difficulties in cognitive strategy application.